Culture and personality - Honigmann,John J. (New York, 1954)
In a young, rapidly expanding field of study the sum and organization of knowledge barely remains unchanged from one issue of a technical journal to the next. Culture and personality is such a field. There is every reason to expect that many things which are said in this book will have to be modified within a relatively short time. Accumulating data may recommend changing certain definitions. Perhaps even the definition of culture and personality, if current approaches expand, will be changed. A few more years of activity as intensive as that which marked the past two or three decades should also provide substantial support for some of the hypotheses which anthropologists entertain today and which are liberally scattered through the following pages. When valid answers to existing questions begin to appear they will not be made solely by anthropologists. Culture and personality is, as the name suggests, a synthetic or a cross-discipline and not an insulated department of social science. In the same way that present knowledge in the field reflects the work of psychologists, psychiatrists, sociologists, and anthropologists, so future results will emerge from the continued integration of ideas from these and other specialists.
Keywords: Social Change